The reproducibility of assessment of white spot lesions adjacent to orthodontic brackets, with a quantitative light induced fluorescence digital camera at different rotations of teeth - an in vitro study - Nicoline C. W. van der Kaaij; Maria J. Faaij; Jacob M. ten Cate; Monique H. van der Veen (BMC, 2018)
Abstract Background A quantitative light-induced fluorescence digital (QLF-D) camera is able to assess demineralizations adjacent to orthodontic brackets. Rotations of teeth during and the presence of the orthodontic appliances may influence the longitudinal follow-up of such lesions over time. Methods Brackets were bonded on extracted teeth: 54 incisors and 31 canines. Demineralizations were formed in vitro directly cervical of the bracket. Images were captured using a QLF-D camera mounted on an optical bench, equipped with a goniometer on a turntable. The teeth were placed in the goniometer simulating buccolingual rotation (0°, 10°, 20°), the turn-table was used for mesiodistal rotations (0°, 10°, 20°). Standardized QLF-D images were made before (with and without a wire) and after debonding at combinations of aforementioned angles of rotation. The image after debonding at 0° buccolingual and 0° mesiodistal rotation served as a control. Results The presence of a bracket resulted in a significantly higher fluorescence loss, yet a smaller lesion area (p < 0.05) in comparison to the control. A significant higher fluorescence loss was seen for rotations towards lingual relative to the 0° buccolingual and 0° mesiodistal rotation, while the effect was less explicit towards buccal. Conclusions Fluorescence loss and lesion size are influenced by the angle of rotation under which the demineralization is photographed. The full extent of demineralizations is only apparent after debonding when photographed at rotations of 0° mesiodistal and up to 20° buccal. Precaution must be taken into account assessing demineralizations of patients undergoing treatment with fixed appliances when using a QLF-D camera.